Reading About Us and Them: Moral but no Minimal Group Effects on Language-Induced Emotion - 't Hart, Björn; Struiksma, Marijn; van Boxtel, Anton; van Berkum, Jos J. A. (Frontiers in Communication, 2021)
Many of our everyday emotional responses are triggered by language, and a full understanding of how people use language therefore also requires an analysis of how words elicit emotion as they are heard or read. We report a facial electromyography experiment in which we recorded corrugator supercilii, or “frowning muscle”, activity to assess how readers processed emotion-describing language in moral and minimal in/outgroup contexts. Participants read sentence-initial phrases like “Mark is angry” or “Mark is happy” after descriptions that defined the character at hand as a good person, a bad person, a member of a minimal ingroup, or a member of a minimal outgroup (realizing the latter two by classifying participants as personality “type P” and having them read about characters of “type P” or “type O”). As in our earlier work, moral group status of the character clearly modulated how readers responded to descriptions of character emotions, with more frowning to “Mark is angry” than to “Mark is happy” when the character had previously been described as morally good, but not when the character had been described as morally bad. Minimal group status, however, did not matter to how the critical phrases were processed, with more frowning to “Mark is angry” than to “Mark is happy” across the board. Our morality-based findings are compatible with a model in which readers use their emotion systems to simultaneously simulate a character’s emotion and evaluate that emotion against their own social standards. The minimal-group result does not contradict this model, but also does not provide new evidence for it.